2007
DOI: 10.1016/j.bcp.2007.01.033
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione depletion and recovery after acute ethanol administration in the aging mouse

Abstract: Glutathione (GSH) plays an important role in the detoxification of ethanol (EtOH) and acute EtOH administration leads to GSH depletion in the liver and other tissues. Aging is also associated with a progressive decline in GSH levels and impairment in GSH biosynthesis in many tissues. Thus, the present study was designed to examine the effects of aging on EtOH-induced depletion and recovery of GSH in different tissues of the C57Bl/6NNIA mouse. EtOH (2-5 g/kg) or saline was administered i.p. to mice of ages 6 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 69 publications
1
30
1
2
Order By: Relevance
“…Speisky et al (1985) found a 35% decrease of the hepatic GSH content at 5 h after administration of ethanol (4 g/kg bw). A recent study conducted by Vogt and Richie (2007) showed that ethanol (5 mg/kg bw) resulted in the significant GSH decrease at 2 and 6 h after exposure, which recovered to the normal level at 24 h. In our study, GSH decreased slightly but had statistical significance in liver tissue homogenate (P < 0.05). The smaller decline might be associated with the examination time.…”
Section: Discussioncontrasting
confidence: 58%
“…Speisky et al (1985) found a 35% decrease of the hepatic GSH content at 5 h after administration of ethanol (4 g/kg bw). A recent study conducted by Vogt and Richie (2007) showed that ethanol (5 mg/kg bw) resulted in the significant GSH decrease at 2 and 6 h after exposure, which recovered to the normal level at 24 h. In our study, GSH decreased slightly but had statistical significance in liver tissue homogenate (P < 0.05). The smaller decline might be associated with the examination time.…”
Section: Discussioncontrasting
confidence: 58%
“…One mechanism for oxidative stress induced GSH depletion may involve enhanced utilization of GSH for the detoxification of free radicals and other oxidants produced as a result of H 2 O 2 exposure (Shaw 1989). Vogt suggested that the increase of lipid peroxidation was not apparent until after GSH levels had been depleted (Vogt and Richie 2007). Astaxanthin can improve the GSH content in both our in vivo and in vitro study.…”
Section: Antioxidant Capacity Analysismentioning
confidence: 64%
“…Acetaldehyde, which is a metabolic product of alcohol, is one substance that reacts with GSH. Alcohol administration leads to GSH depletion in liver and other tissues, 27,28) suggesting direct conjugation of GSH with acetaldehyde and reactive intermediates of alcohol oxidation. 29,30) Other mechanisms by which alcohol induces hepatic GSH depletion include alcohol-induced increased efflux of GSH from the liver 31,32) and enhanced utilization of GSH for detoxification of ROS produced as a result of alcohol administration.…”
Section: Discussionmentioning
confidence: 99%